ChemInform Abstract: Developments and Recent Advancements in the Field of Endogenous Amino Acid Selective Bond Forming Reactions for Bioconjugation. Issue 37 (September 2015) - Koniev, Oleksandr; Wagner, Alain
Abstract Review: 819 refs.